Bottleneck detection for improvement of Emergency Department efficiency. Issue 3 (1st June 2015) - Zhao, Yuancheng; Peng, Qingjin; Strome, Trevor; Weldon, Erin; Zhang, Michael; Chochinov, Alecs
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to introduce a method of the bottleneck detection for Emergency Department (ED) improvement using benchmarking and design of experiments (DOE) in simulation model. Design/methodology/approach – Four procedures of treatments are used to represent ED activities of the patient flow. Simulation modeling is applied as a cost-effective tool to analyze the ED operation. Benchmarking provides the achievable goal for the improvement. DOE speeds up the process of bottleneck search. Findings – It is identified that the long waiting time is accumulated by previous arrival patients waiting for treatment in the ED. Comparing the processing time of each treatment procedure with the benchmark reveals that increasing the treatment time mainly happens in treatment in progress and emergency room holding (ERH) procedures. It also indicates that the to be admitted time caused by the transfer delay is a common case. Research limitations/implications – The current research is conducted in the ED only. Activities in the ERH require a close cooperation of several medical teams to complete patients' condition evaluations. The current model may be extended to the related medical units to improve the model detail. Practical implications – ED overcrowding is an increasingly significant public healthcare problem. Bottlenecks that affect ED overcrowding have to be detected to improve the patient flow. Originality/value – Integration of benchmarking and DOE in simulation modeling proposed in this research shows the promise in time-saving for bottleneck detection of ED operations.